The Study of “Discourse Deixis” in the Short Story “The Garden” by Elisabeth Laird 1979 - Laila, Malikatul; Desla Fitria; Nadiya Veronica; Kharisma Atika Kirani; Eka Wahyu Nugrahani (Universitas Cokroaminoto Palopo, 2023)
This study is about discourse deixis. The main aims of this study are; (1) to identify the forms showing the discourse deixis found in the story, and (2) to analysis the event related by discourse deixis. The data are taken from the short story “The Garden” by Elisabeth Laird (1979). The technique of collecting data are observation and documentation, Technique of analyzing the data refers to the theories of; reading by Cline (2006), identifying by Golden (2017), and describing the data. The underlying theory used in this study is a theory about discourse deixis by Evelyn Hatch (1992). The result show that: (1) the forms showing the discourse deixis are such as follow; noun phrase is the most dominant forms showing the discourse deixis found in the story with percentage of 42,857%, both of adverbial clause of time and sentence have the same percentage as the second forms which are dominant in the story with percentage of 19,047%, sub clause in the short story has a percentage of 9, 523%, prepositional phrase and adverbial of place have the least percentage as forms which are found in the story with percentage of 4,761%. (2) there are 21 events found in the story and there are relations between one event and others. The researchers found that discourse deixis is not only the words this, that, those, these, and then, but discourse deixis is a linguistic indicators with many forms which is connecting one previous event and the next event, where there is a relation between one discourse and the other discourse.